2022
DOI: 10.3389/fpls.2022.870613
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strong Earthquake on Plant Species Composition, Diversity, and Productivity of Alpine Grassland on Qinghai-Tibetan Plateau

Abstract: Earthquakes occur frequently in fragile alpine grassland areas on the Qinghai-Tibet Plateau (QTP), but few studies have evaluated the impacts of seismo-fault of earthquake on alpine grassland vegetation diversity. In this study, we conducted a field survey of plant communities of alpine grassland along the fault zone in the 7.4 Maduo earthquake occurred on 22 May 2021. Surrounding grassland habitat far from the seismo-fault of earthquake was selected as the control. Plant community metrics around and far from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Legumes require higher levels of Ca for the best development ( Broadley et al., 2004 ). This also agrees with our earlier study, i.e., the importance values of legumes decreased significantly after the earthquake rupture ( Zuo et al., 2022 ). Ca levels in plants are highly changeable, but monocots typically have lower Ca concentrations than eudicots, suggesting that low Ca concentrations are more suitable for the growth of monocots like grasses ( Broadley et al., 2003 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Legumes require higher levels of Ca for the best development ( Broadley et al., 2004 ). This also agrees with our earlier study, i.e., the importance values of legumes decreased significantly after the earthquake rupture ( Zuo et al., 2022 ). Ca levels in plants are highly changeable, but monocots typically have lower Ca concentrations than eudicots, suggesting that low Ca concentrations are more suitable for the growth of monocots like grasses ( Broadley et al., 2003 ).…”
Section: Discussionsupporting
confidence: 93%
“…The Maduo earthquake was the biggest earthquake on the Chinese mainland following the Wenchuan earthquake in 2008. The earthquake fault spread bilaterally toward both the east and the west, with a rupture length of approximately 170 km and a duration of approximately 38 s, causing the formation of several new seismic fault zones that severely endangered the fragile alpine grassland ecosystem ( Feng et al., 2022 ; Zhang et al., 2022 ; Zuo et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…occurring in 4 to 5 years but now every month it probably happens. Due to earthquakes lots of forest decaying problem arises like plant community shift, Species loss, and productivity reduction of alpine grasslands [2]. Flood is also one crucial factor to decrease the vegetation area but it is also found that initially, floods affected crops but later crop productivity and fertile land improved and resulted in dense vegetation area [3].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the articles in this SI reveal the driving mechanism of the impact of climate change and human activities ( Dai et al., 2022 ; Hua et al. (2022) ; Ma et al., 2022 ; Zuo et al., 2022 ) on alpine ecosystems with field observations and manipulative experiments combined with new experimental technologies ( Chen et al., 2022 ; Qin et al., 2022 ; Zou et al., 2022 ). Experimental warming enhanced the pattern of the plant allometric growth and promoted migration of the soil stoichiometric characteristics to deep layers in Beiluhe ( Xu et al., 2022 ).…”
mentioning
confidence: 99%